Trapezial Topography in Thumb Carpometacarpal Arthritis - Van Nortwick, Sarah; Berger, Aaron; Cheng, Robert; Lee, Julia; Ladd, Amy L. (Journal of Wrist Surgery, 2013)
Objective Contradictory reported arthritic patterns of the metacarpal surface of the trapezium include preferential volar wear, radial wear, and dorsal-ulnar sparing. We investigated whether a predominant wear pattern exists in surgical trapeziectomy for advanced thumb carpometacarpal (CMC) arthritis.Methods We examined 36 intact trapezia from 34 thumb CMC arthroplasty patients over an 18-month period. The first metacarpal articular surface revealed three consistent morphology patterns: (1) saddle, (2) dish, and (3) cirque. The saddle represented cartilage loss with preservation of the normal trapezial morphology. The dish shape represented concave curvature, with loss of the normal saddle configuration. The cirque shape represented preferential volar concave wear, disrupting the convex volardorsal arc. Two surgeons classified the randomized specimens twice, blinded to patient identity and each other's categorization. Radiographic Eaton staging was correlated retrospectively for 35 of 36 of the trapezial specimens. Eight specimens were further quantified with micro-computed tomography (micro-CT).Results Thirty-six trapezia were classified as follows: 17 (47%) saddle, 12 (33%) dish, and 7 (19%) cirque. Intra-rater reliability was 0.97 and 0.95; inter-rater reliability in the second round was 0.95. The 36 trapezia represented 27 female (75%) and 9 male (25%) patients; 18 (50%) represented the dominant hand. Age at surgery averaged 64 (33–76). Complete cartilage loss of the entire metacarpal surface was seen in 15 (42%) of all specimens. Osteophyte presence was typically minimal in the saddle group; the dish group had characteristic extensive rimming osteophytes in a 91% female population (11/12), and the cirque group had volar osteophytes. Radiographic severity ranged from Eaton stage II to IV; less severe radiographic staging (Eaton II) predominated in the saddle configuration; advanced Eaton III–IV disease predominated in both cirque and dish shapes. Micro-CT verified the three discrete shapes with volardorsal and radioulnar orientation measurements.Conclusion The metacarpal surface of the trapezium demonstrates three distinct patterns of wear in arthritic surgical specimens. Sex, dominance, age distribution, and Eaton stage varied across the different shapes.Level of Evidence Level 3Study Type Observational
Keywords: Trapezium; CMC arthritis; abnormal loading; bone morphology